Mycoflora of leaf rot affected coconut palms - and M. KOCHU BABU, N. SRINIVASAN, M. GUNASEKARAN, ROHINI IYER, R. CHANDRAMOHANAN (Indian Phytopathology, 2002)
The coconut palm (Cocos nucifera L.) is prone to different diseases in India. Leaf rot disease commonly occurs superimposed on root (wilt) disease affected palms in Kerala State. The disease usually appears in the emerging spindle leaves as tiny water soaked lesions, which later coalesce developing into rotting of tender tissues. The disease has been attributed to fungal etiology. In leaf rot diseased palms, profuse fungal mycelial growth and spore masses are commonly visible over the lesions/ necrotic tissues of the leaflet surface and specially between the infected leaflets of unopened spindles. No study has been made earlier on the leaf surface mycoflora of leaf rot disease. An attempt, therefore, has been made to record the prevalence of different mycoflora on leaflets of diseased spindles and leaves.